Multicausal analysis on psychosocial and lifestyle factors among patients undergoing assisted reproductive therapy - with special regard to self-reported and objective measures of pre-treatment habitual physical activity - Viktória Prémusz; Alexandra Makai; Beatrix Perjés; Orsolya Máté; Márta Hock; Pongrác Ács; Miklós Koppán; József Bódis; Ákos Várnagy; Kinga Lampek (BMC, 2021)
Abstract Background National, regional and global trends in prevalence of infertility indicate its public health importance, however it effects various life dimensions of individuals and couples as well. Lifestyle habits may counteract with these factors. The aim of the study was the multicausal analysis of psychosocial and lifestyle factors undergoing assisted reproductive therapy (ART) with special regard to pre-treatment habitual physical activity (PA). Methods In a cross-sectional, observational cohort study on ART patients (N = 60, age 34.6 ± 5.2 years, BMI 24.2 ± 4.9 kg/m2) with follow up on outcome measures a detailed description was given on PA patterns (ActriGraph GT3X, GPAQ-H) and on general and infertility related distress (BDI-13, FPI). Results Respondents reported normal mood state (BDI-13) but moderately high infertility-related distress (FPI) in Social- and very high distress in Sexual Concern. It was revealed that time spent with recreational PA (RPA) could counteract with infertility-related distress (Social Concern R = -0.378, p = 0.013; Relationship Concern R = -0.365, p = 0.019). In the presence of clinical pregnancy GPAQ-H RPA MET was significantly higher (p = 0.048), in the non-pregnant group cumulative values and work-related PA were higher. Correlations could be found between RPA time and the number of oocytes (R = 0.315, p = 0.045), matured oocytes (R = 0.339, p = 0.030) and embryos (R = 0.294, p = 0.062) by women who reached at least 150 min RPA (GPAQ-H). Multivariate linear regression revealed that the number of oocytes was positively influenced by the GPAQ-H recreation MET (R 2  = 0.367; F = 10.994, p = 0.004; B = 0.005, p = 0.004, B Constant = 4.604). Regarding the number of embryos (R 2  = 0.757, F = 17.692, p < 0.001, B Constant = 1.342) positive relationship was found with GPAQ-H RPA MET (B = 0.004, p < 0.001) and negative with BMI (B = -0.167, p = 0.038). It was disclosed (R 2  = 0.958, F = 408.479, p < 0.001) that higher Very Vigorous Activity (ActiGraph) was accompanied with higher hCG (B = 63.703, p ≤ 0.001). However, time spent with moderate PA (GPAQ-H) (B = 0.002, SE = 0.001, Wald = 3.944, p = 0.047, OR = 1.002) was significantly associated with live births. Conclusions Amount of PA alone did not have a positive effect on outcome of ART. Type and intensity seemed to be more significant. Existing differences in response to infertility due to recreational PA suggest the importance of the development of a specific intervention. The robust overestimation of PA in self-reports highlights the need to improve physical literacy of women undergoing ART.